Pengaruh Kualitas Pelayanan, Sanksi Perpajakan, Biaya Kepatuhan Pajak, Penerapan E-Filing Dan Pengetahuan Pajak Terhadap Kepatuhan Wajib Pajak (Studi Empiris Pada KPP Pratama Surakarta) - Novi Endaryanti, Ratih; , Dra. Mujiyati, M.Si (2017)
This study, entitled "Effects of service quality, tax penalties, tax compliance costs, the implementation of e-filing and tax knowledge to the Taxpayer Compliance OP in Surakarta Tax Office Primary". The purpose of this study was to determine the effect of service quality, tax penalties, tax compliance costs, the implementation of e-filing and tax knowledge to the Taxpayer Compliance OP in Surakarta Tax Office. This study uses primary data in the form of a questionnaire given to the taxpayer listed on STO Surakarta. The samples used were 100 respondents, the sampling method in this study is Non Probability sampling is random sampling were selected randomly. Data analysis technique used is multiple linear regression analysis and the data obtained were processed using SPSS statistical software. Based on the research results and knowledge service quality tax compliance does not affect the WP OP. While the tax penalties and the implementation of e-filing positive effect on compliance WP OP, and tax compliance costs negatively affect WP OP.